The significance of major and stable molecular responses in chronic myeloid leukemia in the tyrosine kinase inhibitor era - Renault,Ilana Zalcberg (2011)
Tyrosine kinase inhibitors have changed the management and outcomes of chronic myeloid leukemia patients. Quantitative polymerase chain reaction is used to monitor molecular responses to tyrosine kinase inhibitors. Molecular monitoring represents the most sensitive tool to judge chronic myeloid leukemia disease course and allows early detection of relapse. Evidence of achieving molecular response is important for several reasons: 1. early molecular response is associated with major molecular response rates at 18-24 months; 2. patients achieving major molecular response are less likely to lose their complete cytogenetic response; 3. a durable, stable major molecular response is associated with increased progression-free survival. However, standardization of molecular techniques is still challenging.